Mass mortality of pen shell Atrina maura (Bivalvia: Pinnidae) due to abrupt population increase of tunicate (Distaplia sp.) in a subtropical bay, Mexico. (5th October 2021) - Moreno-Dávila, Betzabé; Gómez-Gutiérrez, Jaime; Alcoverro, Teresa; Ramírez-Luna, Silvia; Sánchez, Carlos; Balart, Eduardo F.; Huato-Soberanis, Leonardo
Abstract: The present study analyses the coverage of epibiont Distaplia cf. stylifera (Ascidiacea: Holozoidae) and five environmental variables (Sal, SST, DO, sea surface Chl- a concentration and pH) as potential factors to explain a mass mortality event in a restored population of the pen shell Atrina maura (Bivalvia: Pinnidae) in a subtropical bay of the Gulf of California, Mexico. Annual autumn surveys in 2015, 2016 and 2017 (Nov–Dec) and an additional summer survey in 2016 (Jun) showed that the tunicate was first observed at low densities in a few sampling sites during 2015 and rapidly expanded along the pen shell banks in 2016. Tunicate manual removal was carried out in two small areas during Sep-Nov 2016 and Jan–Mar 2017. The mass mortalities of A. maura detected in 2016 and 2017 resulted in a high economic loss for regional fishers. A Generalised additive model (GAM) indicated that the substrate provided by A. maura was the only significant factor associated to the rapid expansion (measured as the proportion of coverage) of D. cf . stylifera . Paradoxically, the recovery success in the A. maura population increased substrate availability for the tunicate epibiont, facilitating an abrupt and fast colonisation process on the pen shell banks, resulting in A. maura mass mortality events in 2016 and 2017. Our model predicts that D . cf. stylifera coverage effects begin to occur when the density of A. maura is > 47 inds./250 m 2 . A second GAM demonstrated that the main driver of A. maura mortality was ascidian coverage, and salinity, SST and DO were secondary driver factors. We concluded that the density of dead A. maura increases when the coverage of D. cf. stylifera is >8%, salinity >37.3 PSU, SST <26.9 °C and DO > 5.06 mg O2 /L. Early harvesting of A. maura to decrease substrate availability at the first signs of D. cf . stylifera population growth can avoid significant economic losses in the future. Highlights: Protection of Atrina maura increased substrate availability facilitating an abrupt population growth of tunicate Distaplia. cf . stylifera. The coverage of D. cf . stylifera, salinity, sea surface temperature and dissolved oxygen concentration were related with A. maura mass mortality. Coverage of the tunicate D. cf . stylifera decreased from 2016 to 2017 likely associated with storms that decreased salinity. Increased distance among pen shell banks and harvesting at the first signs of tunicate population growth can avoid significant economic losses.